Performance data analysis of Greco-Roman wrestling matches of the 2019 European Championships - Roklicer, R.; Dokmanac, M.; Curby, D. G.; Lakicevic, N.; Trivic, T.; Baic, M.; Drid, P. (International Journal of Wrestling Science, 2020)
Wrestling is recognized as a vigorous, intermittent and weight categorized combat sport. For the purpose of revealing essential information for development of sport- specific preparation of wrestlers, technical-tactical and physiological demands analyses of wrestling matches are critical for elite level athletes. The aim of this study was to present analyzed technical-tactical scoring actions in Greco-Roman wrestling in the 2019 Senior European Championship via a novel Performance Data Analysis. Results of this study indicated the prevalence of points scored from standing position compared to parterre actions. Additionally, higher percentage of total points scored were achieved due to technical points in comparison with other points scored, 71.37% vs 28.63%, respectively. Implementing Performance Data Analysis could facilitate the understanding and following of a wrestling match. Furthermore, it could help coaching staff to obtain the relevant wrestling-specific data, and that way, to help athletes getting prepared for upcoming competitions.